Case reportAngiosarcoma of the scalp: a case report - Wittych, Justyna; Banatkiewicz, Pawel; Wachowicz, Marta; Pruska-Pich, Dorota; Mitura, Stanislaw; Gisterek, Iwona (Journal of Contemporary Brachytherapy, 2014)
Purpose: The aim of this paper is to report the treatment of angiosarcoma of the scalp. High-dose-rate (HDR) brachytherapy with an individual mold applicator is presented. Case description: A case of a 75-year-old male will be presented with multicentric lesions over the scalp in the temple and crown region. Biopsy diagnosis was angiosarcoma of the scalp, nonoperable. The patient was qualified for chemotherapy combined with radiotherapy. Discussion : Angiosarcoma of the scalp is a very aggressive tumor. The main aim of the treatment of angiosarcoma is local control of the tumor. Most cases are treated with wide excision surgery. The use of surgery with adjuvant radiotherapy or chemotherapy is recommended in some cases. Chemotherapy and radiotherapy are suggested in the recurrent or extensive lesions with regional or distant metastasis. Radiation therapy can be realized with external beam therapy or brachytherapy. High-dose-rate brachytherapy is an effective, adequate, well tolerated by patients treatment method. In every case, an individual approach is needed. Conclusions : The HDR brachytherapy technique is useful and practicable. The advantages of brachytherapy are: targeted dose distribution, low integral dose, and short time of treatment. The mold HDR brachytherapy treatment using an individual applicator was an appropriate tool for the presented patient.